The decalogue as a guide for Yorùbá Christian ethics - Ogunkunle, Caleb O. (Ilorin journal of religious studies, 2018)
The level of moral decadence in many African nations is a serious concern to several people, especially biblical scholars. One suspect is a gross violation of ethical principles and values as contained in the Bible. The result of the violation of ethical norms is lack of peace and harmony in many societies and communities in Africa, as there are several cases of wickedness such as stealing, killing and kidnapping among others. This paper examines the Decalogue as an ethical guide for Yorùbá Christians, with the purpose of linking Yorùbá Christian ethics with the Decalogue, the Ten Words which Yahweh gave to Moses on Mount Sinai and to remind Yorùbá Christians of the need to follow the ethical principles contained in the Bible. Historico-exegetical method is adopted. Historically, literature on Decalogue and Yorùbá Christian ethics is reviewed. Exegetically, some key Hebrew words in the Biblical texts are studied with the help of Hebrew Lexicon and Theological Wordbook of the Old Testament. It is discovered that Decalogue is a divine revelation of God to Moses for the Israelites and their obedience to it brought blessings while disobedience brought curses as seen later in their history. Also, there is a strong connection between the Decalogue and different laws found in different societies in Africa. The paper concludes that just as the Decalogue was to the Israelites, so the Bible must be to the Yorùbá Christians. Therefore, Yorùbá Christians must adhere and obey the instructions contained in the Bible including the Declogue, so as to aide reduction in the ethical problems confronting the (Yoruba) society.Keywords: Decalogue, Ten Commandments, Christians, Ethics, Yorùbá, Nigeria